Are experience and schooling complementary?: evidence from migrants' assimilation in the Bangkok labor market - Yamauchi, Futoshi (International Food Policy Research Institute, 2003)
This paper aims to empirically identify migrants' assimilation process by examining their wage dynamics in one urban labor market of a developing country: Bangkok, Thailand. Although prior studies on migration highlight the effects of schooling on the decision to move and the resulting selectivity of migrant populations, the role of schooling in the assimilation process has not been thoroughly examined in the context of urban labor markets.